BEDHAYA KINJENG WESI DANCE CREATION IN THE PERSPECTIVE OF HYBRIDITY AND AUTHENTICITY - Witjaksono, Bambang (ARTISTIC : International Journal of Creation and Innovation, 2025)
Bedhaya Kinjeng Wesi dance was created as a reference in the process of making the Bedhaya Kinjeng Wesi sculpture, which is installed in the boarding lounge of Yogyakarta International Airport. Kinjeng Wesi is a Javanese term meaning airplane. This study aims to find out the extent of hybridity and authenticity of Bedhaya Kinjeng Wesi dance. The method used is descriptive qualitative analytical by describing the work of art on the aspects of hybridity and authenticity. The elements of hybridity and authenticity in Bedhaya Kinjeng Wesi dance proved to be a mimicry that displays ambivalence because on the one hand it wants to build a common identity with elements of locality, but on the other hand it tries to maintain its differences.